Morphological criteria for prognosis in patients with melanoma - I. Yakovtsova; V. Sadchikov; M. Sadchikova; O. Dolgaya; A. Oleynik; S. Danilyuk; N. Ivanyuta (Zaporozhye State Medical University, 2012)
Among the morphological criteria of prognosis in patients with melanoma of the skin the most important ones are thickness, depth of invasion, ulceration of the tumor, the presence of microsatellites and metastases in regional lymph nodes, the severity of the proliferative activity of tumor cell invasion into blood vessels. The value of clinical, anatomical and cell-type variant of melanoma, the degree of pigmentation, the severity of her infl ammatory infi ltration, fi broplasia, signs of regression is controversial.